The dilemma of managing childhood poisoning without adequate history in a resource-poor environment: Report of 4 cases - Akhiwu, Helen; Ibrahim, Jamila; Abdullahi, Shehu; Akibu, Oyelami (Nigerian Journal of Basic and Clinical Sciences, 2026)
The dilemma of managing childhood poisoning without adequate history poses a serious challenge, especially in resource-limited settings where facilities for toxicology studies are not readily available. We reported 4 cases of childhood accidental poisoning who were admitted to our center with inadequate history. Two were cases of haloperidol poisoning, another was that of potassium bromate poisoning and the fourth was that of organophosphate poisoning. While meticulous history was helpful in the making of the diagnosis of the first 3 cases, the use of electronic literature solved the riddle in the fourth.
Keywords: Childhood; inadequate history; poisoning